Prevalence of Fungi With Seeds of Twenty Brri Released Rice Varieties and Seed Quality Analysis (Journal of the Asiatic Society of Bangladesh, Science, 2018)
A total of 20 rice varieties of BRRI dhan 56 to BRRI dhan 75 were collected from Bangladesh Rice Research Institute (BRRI) for seed quality analysis, detection and identification of fungi associated with seeds of selected rice varieties. Dry inspection indicated that the percentage of pure seeds ranged from 90 - 100. The highest percentage of pure seed was found in BRRI dhan 66 and BRRI dhan 70 (100) and lowest in BRRI dhan 68 (90). A total of 21 fungal species were isolated from the selected rice varieties following “Blotter and Tissue Planting” methods. They were Alternaria padwickii, A. tenuissima, Aspergillus flavus, A. fumigatus, A. niger, A. ochraceus, A. clavatus, A. terreus, Bipolaris sorokiniana, B. spicifera, Chaetomium globosum, Curvularia lunata, Drechslera oryzae, Fusarium sp.1, Fusarium sp. 2, Nigrospora sp., Penicillium sp., Pestalotiopsis guepinii, Rhizopus stolonifer, Syncephalastrum racemosum and Trichoderma viride. Among them Penicillium sp., Drechslera oryzae, Aspergillus ochraceus, A. flavus, A. fumigatus, A. niger and Fusarium sp.1 were predominant in most of the rice varieties. In Tissue Planting method Drechslera oryzae showed the highest mean per cent frequency (6.69) and lowest was in the Bipolaris sorokiniana (0.41). Maximum total fungal association was recorded in variety BRRI dhan 61 (156.79%) and minimum in BRRI dhan 66 (24.69%). In Blotter method Penicillium sp. showed the highest mean per cent frequency (7.56) and lowest was in Rhizopus stolonifer (1.71). Maximum total fungal association was recorded in BRRI dhan 63 (147.37%) and minimum in BRRI dhan 65 (19.21%). Germination percentage of seeds was highest in BRRI dhan 66 (88) followed by BRRI dhan 67 (82), BRRI dhan 74 (80) and lowest in BRRI dhan69 (24). The percentage of seedling mortality was highest in BRRI dhan 63 (42) and lowest in BRRI dhan 74 (8.0) followed by BRRI dhan 67 (10). Correlation coefficient and regression analysis indicated that prevalence of fungi has significant effect on seed germination and seedling mortality. The present research work suggests that out of 20 BRRI rice varieties, BRRI dhan 65, BRRI dhan 66, BRRI dhan 67 and BRRI dhan 74 showed better performances on the basis of percentage of pure seed, fungal association, seed germination and seedling mortality.Asiat. Soc. Bangladesh, Sci. 44(1): 79-89, June 2018